Swedish-Finnish dictionary: Attachment and sale, and liquidation words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Finnish glossary containing attachment, sale, and liquidation words. Published in Kieliviesti 1/2007. Contains approximately 160 entries. 2007.

Swedish-Finnish dictionary containing attachment and sale, and liquidation words. Published in Kieliviesti 1/2007. Contains approximately 160 entries. 2007.

Svensk-sverigefinsk ordlista med utmätnings- och konkursord. Publicerades i Kieliviesti 1/2007. Innehåller ca 160 ord. 2007.
Svensk-finsk ordlista: utmätnings- och konkursord
Keywords: languages; språk; Linguistics; Språkvetenskap; Bankruptcy; Konkurs; word list; ordlista; language documentation; språkdokumentation; ECONOMICS; EKONOMI; Language and linguistics; Språk och lingvistik; Business Administration; Företagsekonomi; Languages and Literature; Språk och litteratur